Dobutamine stress echocardiography in pulmonary arterial hypertension. (1st November 2018) - Ghio, Stefano; Fortuni, Federico; Greco, Alessandra; Turco, Annalisa; Lombardi, Carlo; Scelsi, Laura; Raineri, Claudia; Matrone, Benedetta; Vullo, Eleonora; Guida, Stefania; Badagliacca, Roberto; Oltrona Visconti, Luigi
Abstract: Background: There is a growing interest in exploring the concept of right ventricular functional reserve in patients with pulmonary arterial hypertension. However, it is still unclear how it should be assessed. Aim of the study was to investigate the determinants of the changes in cardiac output and in pulmonary pressure during dobutamine stress echocardiography in pulmonary arterial hypertension. Methods: Low-dose dobutamine stress echocardiography was performed in 55 patients and 28 controls. Tricuspid annular plane systolic excursion, its ratio to systolic pulmonary artery pressure, right ventricular area change, degree of tricuspid regurgitation, right ventricular end-systolic pressure-area ratio, cardiac output were assessed at rest and at peak stress. Results: According to the stress induced increase in cardiac output, patients were classified into 2 groups: above/equal to the median of 2.8 L/min (high cardiac output) or below the median (low cardiac output). High cardiac output patients were characterized by a greater increase in heart rate (+45.1 ± 17.5 vs +21.3 ± 17.7 bpm), a greater improvement in tricuspid annular plane systolic excursion (+4.2 ± 3.3 vs +1.9 ± 2.6 mm, P = 0.005) and a decrease in tricuspid regurgitation (P = 0.010) as compared to low cardiac output patients. Changes in pulmonary pressure were not associated with changes in indicators of right ventricular function but only with changes in heart rate. Conclusions: The increase in cardiac output during dobutamine is associated with an improvement in longitudinal right ventricular function, a decrease in tricuspid regurgitation and an increase in heart rate. Changes in pulmonary pressure only reflect the changes in heart rate. Highlights: Dobutamine echocardiography may disclose right ventricular reserve in PAH. TAPSE and tricuspid regurgitation are the relevant echocardiographic parameters. Changes in pulmonary pressure depend on the chronotropic response.